2016
DOI: 10.1016/j.biocel.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α induces vascular endothelial cells apoptosis through overexpressing pregnancy induced noncoding RNA in Kawasaki disease model

Abstract: Kawasaki disease (KD) is an autoimmune disease in which the medium-sized blood vessels throughout the body become inflamed. The increased evidences showed that TNF-α was association with vascular inflammation in KD patients. However the detailed mechanism was still unclear. Recent studies indicated abnormal expressed long non-coding RNAs (LncRNAs) involved in many diseases. Thus the purpose of this study is to explore the role of lncRNAs in KD and find out the new target for KD treatment. In this study, firstl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Since AQP-1, MMP9, and JAM-C all play key roles in regulating capillary permeability in SAP [9-11], we also observed changes in the expression of endothelial barrier function-related proteins such as AQP-1, MMP-9, and JAM-C proteins and mRNA. We found that after adding TNF-α (10 ng/mL), the TEER permeability measurements and apoptosis rates of the endothelial cells increased at 6 h, 12 h, and 24 h. These results are consistent with the results of our previous study [22]. The most significant rise in the rate of apoptosis took place at 12 h, so we chose 12 h as a check point.…”
Section: Discussionsupporting
confidence: 81%
“…Since AQP-1, MMP9, and JAM-C all play key roles in regulating capillary permeability in SAP [9-11], we also observed changes in the expression of endothelial barrier function-related proteins such as AQP-1, MMP-9, and JAM-C proteins and mRNA. We found that after adding TNF-α (10 ng/mL), the TEER permeability measurements and apoptosis rates of the endothelial cells increased at 6 h, 12 h, and 24 h. These results are consistent with the results of our previous study [22]. The most significant rise in the rate of apoptosis took place at 12 h, so we chose 12 h as a check point.…”
Section: Discussionsupporting
confidence: 81%
“…For example, in Kawasaki disease, TNF-α induces vascular endothelial cell apoptosis by causing the overexpression of pregnancy-induced non-coding RNA49. Here, E. coli -induced cytokines, such as TNF-α, IL-1β, IL-6, IL-8, GRO-α and MIP-2, were selected to stimulate the primary hBMECs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, low-intensity exercise was not enough to decrease the systemic expression level of inflammatory cytokines. However, increased TNF-a could promote vascular endothelial cell apoptosis (40). Therefore, capillary regression was induced rapidly and drastically by increased TNF-a through promoted vascular endothelial cell apoptosis in cancer cachexia.…”
Section: Discussionmentioning
confidence: 99%